An Intern's Experience at the Great Lakes Resources Sharing Conference. Issue 3 (15th May 2017) - Allen, Kristin
ABSTRACT: This article chronicles the involvement of an intern working and attending the 2017 Great Lakes Resource Sharing Conference (GLRSC) in Oak Brook, Illinois. GLRSC primarily targets library professionals interested in various forms of cross collaboration within their communities and/or college campuses. Ideas in the areas of open educational resources (OER) and new strategies for interlibrary loan were discussed. As part of the planning process, the interns were required to attend virtual planning meetings, to set up the signage and technology, and to provide social media and technical support during the presentations. This was a positive experience to those interested in emerging technologies and differing avenues of resource sharing, and was also great exposure to the practice of organizing a large-scale library conference.